Editorial (Bangladesh Journal of Bioethics, 2020)
Cambridge online dictionary offers the meaning of the noun term “environment” as the air, water, and land in or on which humans, animals, and plants reside1. The environment can also be mixture of factors that influence both organic and inorganic ecosystems and their shared co-existence. This co-existence is the last idea that is given significance in the sophisticated and busy life styles of the modern day. In other words, in our own attitudes lies a large portion of causal conditions for outward environmental disruptions and imbalances. The challenges we face globally have their origin in local settings, the threats we face at the surface level of our location have their origins at 'deep level' in our very own way of living, in the very way of our behaviour towards others. With this absence of senses, species of human beings not only put themselves at risk, but also put other species of life in danger all over the world. It can be said that the ecological sufferings what we are experiencing today are seemed to have deep roots in anthropocentric views about the dominion of humans on earth. Without major societal changes, including changes in the habits of human beings, these exploitative, consumerist practices cannot be resolved 2.The papers in this issue on Environmental Ethics emphasize the need of the sense of morality towards the surrounding environment.